Variation in cell-associated unspliced HIV RNA on antiretroviral therapy is associated with the circadian regulator brain-and-muscle-ARNT-like-1. (24th September 2018) - Chang, Christina C.; Naranbhai, Vivek; Stern, Jared; Roche, Michael; Dantanarayana, Ashanti; Ke, Ruian; Tennakoon, Surekha; Solomon, Ajantha; Hoh, Rebecca; Hartogensis, Wendy; Hecht, Frederick M.; Sikaris, Ken; et al.
Abstract : Objective(s): To determine whether variation in cell-associated unspliced (CA-US) HIV RNA in HIV-infected individuals on antiretroviral therapy (ART) has a circadian basis. Methods: Prospective observational study of HIV-infected individuals on ART. Blood was collected on three occasions and CA-US HIV RNA and mRNA of the circadian-locomotor-output-cycles-kaput (CLOCK)-associated genes quantified by real time PCR. CLOCK-associated proteins were over-expressed in a cell line stably transfected with an HIV long-terminal repeat (LTR) luciferase reporter. Results: Using a mixed effects model, there was a significant increase in log-CA-US RNA at the third visit compared with the first visit (effect size of 0.619 with standard error (SE) of 0.098, P < 0.001) and an independent effect of time of blood draw (effect size 0.051 (SE 0.025), P = 0.040). The CLOCK-associated gene, brain-and-muscle-ARNT-like-1 ( BMAL-1 ) had a significant relationship with log CA-US HIV RNA (effect size 8.508 (SE 3.777), P = 0.028) and also with time ( P = 0.045). Over expression of BMAL-1 and CLOCK in a cell line stably transfected with an HIV-LTR luciferase reporter resulted in an increase in luciferase expression and this was reduced following mutation of the second E-box in the HIV-LTR. Conclusion: The basal level of HIV transcription on ART can vary significantly and is modulated by the circadian regulator BMAL-1, amongst other factors. Abstract : Supplemental Digital Content is available in the text